Pengaruh Penggunaan Beban Lampu Terhadap Unjuk Kerja Cooler Box Portable - Dewayana, Dicky Mahaputra; Astika, I Made; Sucipta, Made (Teknik Desain Mekanika, 2022)
Abstract Indonesia's marine resources are the main source of income for fishermen, namely fish. The freshness of fish is the main factor determining the selling price. To maintain the freshness of fish, traditional fishermen often use preservatives. The use of a portable cooler box was chosen because it does not require electricity and its use only requires ice. In its use, clinical testing is needed to ensure that the portable cooler box that is used will be able to work well with various items that will be placed in it. This study will test the portable cooler box by adding several energy loads in the form of lamps with variations of 15, 25, and 40 watts, to determine the performance value of the portable cooler box. The method used is to test the use of a portable cooler box with added 15-watt, 25-watt, and 40-watt lamps for each test by taking data using the DHT-22 sensor to get the temperature and humidity values. After getting the temperature and humidity values. In experiments using 15-watt lamps, the minimum air temperature that can be achieved is -2.1 °C while the minimum temperature that can be achieved with 25-watt lamps is 4.75 °C, and the minimum temperature that can be achieved with 40-watt lamps is 8, 35 °C. Humidity testing with 15-watt bulbs had higher humidity values than 25 and 40-watt bulbs. Experiments with 15-watt lamps are 65.25% and up to 81.25%, while with 25-watt lamps it is 59.20% and up to 75.20%, and with 40-watt lamps it is 50.55% after that it goes up to 71.80%. Keywords: Cooler Box Portable, Temperature, Humidity.